2023
DOI: 10.1007/s11547-023-01675-w
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors and astrocytic marker for the glymphatic system activity

Abstract: Objectives Glymphatic system maintains brain fluid circulation via active transportation of astrocytic aquaporin-4 in perivascular space. The diffusion tensor imaging analysis along the perivascular space (DTI-ALPS) is an established method measuring perivascular glymphatic activity, but comprehensive investigations into its influential factors are lacking. Methods Community-dwelling older adults underwent brain MRI scans, neuropsychiatric, and multi-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This is also a problem that has been pointed out in a number of papers. 27,28,30,47,61,82,90,163,173,184,185 This problem is an inherent weakness of the ALPS method and cannot be solved. However, other methods discussed in this review also do not evaluate the whole system.…”
Section: Controversy In Dti-alps Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also a problem that has been pointed out in a number of papers. 27,28,30,47,61,82,90,163,173,184,185 This problem is an inherent weakness of the ALPS method and cannot be solved. However, other methods discussed in this review also do not evaluate the whole system.…”
Section: Controversy In Dti-alps Methodsmentioning
confidence: 99%
“…A number of studies using the DTI-ALPS method have evaluated the association between age and ALPSindex. 4,17,18,[27][28][29]36,43,56,61,70,74,78,[80][81][82][83][84][85][86][87][88][89][90][91][92] Among these reports, a number of them showed negative correlations between age and ALPS-index. McKnight et al showed a negative correlation between the ALPS-index and age in a group of subjects with PD or essential tremor aged approximately 40−80 years, with a correlated Spearman's rank correlation coefficient of −0.203.…”
Section: Findings On the Agingmentioning
confidence: 99%
“…The glymphatic system is active during sleep and primarily driven by arterial pulsation and the aquaporin-4 (AQP4) s maintains health by efficiently removing waste products and distributing essential nutrients ( 1 ). The significance of the glymphatic system is stressed by its association with several neurological disorders, including neurodegenerative disorders (NDs), traumatic brain injury, and stroke, among others ( 3 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the lack of a lymphatic system in the brain led to questions about how waste products were removed ( 7 ). The discovery of the glymphatic system revealed a robust waste removal system intimately linked with the brain’s vascular system ( 3 ). This finding has also highlighted the importance of sleep for brain health, given that the glymphatic system is highly active during sleep ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…where the authors observed that a decrease in the ALPS index was correlated with worse cognitive function and an increase in age. 68 Because of the simplicity of the measurement and the ability to retrospectively calculate the ALPS index in large clinical datasets, it has been quickly adopted to study many cerebral health conditions, including neurodegeneration, 68,[93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] cerebrovascular pathologies, [111][112][113][114][115][116][117] hydrocephalus, [118][119][120][121] epilepsy, [122][123][124][125][126][127][128] migraines, 129,130 sleep disorders, [131][132][133][134] and traumatic brain injury. [135][136]…”
Section: The Absence Of Cardiac Gating Can Introduce Dwi Signals Depe...mentioning
confidence: 99%